Multicenter, Prospective, Randomized, Single Blind, Cross-Over Study on the Effect of a Fixed Combination of Citicoline 500 mg Plus Homotaurine 50 mg on Pattern Electroretinogram (PERG) in Patients With Open Angle Glaucoma on Well Controlled Intraocular Pressure - Rossi, Gemma Caterina Maria; Rolle, Teresa; De Silvestri, Annalisa; Sisto, Dario; Mavilio, Alberto; Mirabile, Alessandra Venera; Paviglianiti, Alessia; Strano, Beatrice; Picasso, Erica; Pasinetti, Gian Maria; Milano, Giovanni; Ruberto, Giulio (Frontiers in Medicine, 2022)
Purpose To evaluate the potential beneficial and synergistic effects of oral intake of a fixed combination of citicoline 500 mg plus homotaurine 50 mg (CIT/HOMO) on retinal ganglion cell (RGC) function in subjects with glaucoma using pattern electroretinogram (PERG) and to investigate the effects on visual field and quality of life. Methods Consecutive patients with primary open-angle glaucoma with controlled IOP (<18 mmHg) receiving beta-blockers and prostaglandin analogs alone or as combination therapy (fixed or un-fixed); with stable disease (progression no more than −1 dB/year at the visual field MD); and an early to moderate visual field defect (MD < −12 dB) were randomized to: arm A. topical therapy + CIT/HOMO for 4 months, 2 months of wash out, 4 months of topical therapy alone; arm B. topical therapy alone for 4 months, topical therapy + CIT/HOMO for 4 months, 2 months of wash out. All patients underwent 4 visits: complete ocular examination, visual field, PERG and quality of life assessment (NEI-VFQ25) were performed at each visit. Results Fifty-seven patients completed the study: 26 in group A and 31 in group B. At the end of the intake period, PERG's P50 and N95 waves recorded a greater amplitude. The increase was statistically significant in the inferior and superior P50 waves amplitude: 0.47 μV (95%CI, 0.02–0.93; p = 0.04) and 0.65 μV (95% CI, 0.16–1.13; p = 0.009), respectively, and in the inferior N95 wave amplitude 0.63 μV (95% CI, 0.22–1.04; p = 0.002). A significantly shorter peak time of 3.3 μV (95% CI, −6.01– −0.54; p = 0.01) was observed for the superior P50 wave only. Conclusions Daily oral intake of the fixed combination CIT/HOMO for 4 months improved the function of inner retinal cells recorded by PERG in the inferior and in the superior quadrants, independently from IOP reduction. This interesting association could represent a valid option for practicing neuromodulation in patients with glaucoma to prevent disease progression.